PENGARUH PROBLEM BASED LEARNING BERBANTUAN POWERPOINT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Alvira Amalia Ananda; Firmansyah Firmansyah (JURNAL MATHEMATIC PAEDAGOGIC, 2023)
The purpose of this research is to analyze the effect of the problem based learning model assisted by PowerPoint media on students mathematical problem solving ability. This type of research is a quasi experiment with a posttest-only design. The population in this study was class VIII MTs. LAB IKIP Al-Washliyah Medan. The sampling technique, namely cluster randam sampling, was obtained by two classes, namely class VIII-A with 30 students being the experimental class and class VIII-B with 31 students being the control class. The test applied to obtain data is a test of mathematical problem solving ability in the form of a description. The test is the posstest which is carried out after the treatment is given. The results of the study found that the significance value of the t-test was 0,000 < 0,05. From the results of testing the hypothesis,  is obtained, namely  meaning that H0 is rejected and Ha is accepted. The conclusion obtained  is an effect of the problem based learning model assisted by PowerPoint media on the mathematical problem solving ability of students in MTs. LAB IKIP Al-Washliyah Medan.Keywords: Problem Based Learning, PowerPoint, Mathematical Problem Solving Ability